Factors Associated with Joint Diseases in The Coastal Community of Laha Village in Ambon, Indonesia - Augie Desvie Klausya Kadun; Christiana Rialine Titaley; Annastasia Eklesia Ohoiulun; Filda Vionita Irene de L ima; Ninik Ma’athia Sallatalohy; Fadila Tri Starlia; Maxwell Landri Vers Malakauseya; Etrin Zulqarnain Eka Saputra Linggar; Noviyanter Siahaya (Future Science, 2023)
Joint diseases have remained a public health concern in the world for decades. These conditions are not only experienced by the elderly but can also occur at a relatively young age. The research objective was to analyze the factors associated with joint disease in the Laha Village in Ambon City. Data were derived from a household health survey in the Laha Village, Ambon City coastal area, in 2022. The dependent variable in this study was the occurrence of joint disease, with the independent variables consisting of demographic status, lifestyle, and dietary patterns. Data analysis used the multivariate logistic regression method. In this study, the prevalence of joint disease in coastal communities in Laha Village was 14.8%. The results of data analysis showed that demographic factors that were significantly related to joint disease were: respondents’ age of 60-71 years (aOR=19.74; 95CI%:7.01-16.66; p<0.001) and those who did not work outside the house (aOR=2.00; 95 CI%: 1.0 -3.94;p=0.041). A significant association was found between joint diseases and those who did not smoke cigarettes (aOR=3.85; 95%CI: 1.65-8.98; p=0.002). We also found that joint disease was also associated with dietary patterns, which were the habit of rarely consuming meat (aOR=2.77; 95 CI%: 1.26-6.10; p=0.011) and the habit of not consuming soft drinks (aOR=2.86; 95 CI%: 1.19-6.86; p=0.012). However, not consuming salty foods reduced the likelihood of developing joint disease (aOR=0.35; 95% CI: 0.13-0.94; p=0.038). The results of this study demonstrated the importance of having a healthy lifestyle and balanced diet to reduce the incidence of joint disease.